BARBIE DOLL AND JANAKI AMMAL: CAREERS OF WOMEN IN SCIENCE - Nikalje, Varada M. (SCHOOL SCIENCE, 2014)
March eight is celebrated as Women’s day throughout the world. Numerous schemes for the betterment of women are launched, and the contribution of women to society is lauded. In March 2013, the National Council of Educational Research and Training (NCERT) New Delhi, marked the occasion by re-naming one of the buildings of NCERT. Earlier referred to ubiquituously as the Science Block, the building was henceforth to be known as ‘Janaki Ammal Block’. A small, almost innocuous step, but one that had a ripple effect. ‘Janaki Ammal who?’ was the reaction of most colleagues and friends. We made a beeline for the Internet, firm in the belief “Don’t think, just Google!’. We saw the image of a wrinkled, intelligent face, a replica of which would be later embossed on the outer wall of the building. We learnt that Ammal was born in 1897, that she had studied abroad, that she later returned to India to become a Professor of Botany, and that Pandit Nehru, the then Prime Minister of India, invited her to accept an assignment as Special Officer to re-organise the Botanical Survey of India. She devoted her energy and enthusiasm to science, which, to her, was both a profession and a passion. As the poet Robert Frost puts it, if one works at what one loves, life becomes a fulfilment: